Effects of Hypoxia Stress on Biochemical Indices and Expression of Hypoxia-Related Genes in the Heart of Rainbow Trout (Oncorhynchus mykiss) - Jiuju MA; Jinqiang HUANG; Yongjuan LI; Shenji WU; Lu ZHAO; Yue ZENG (Progress in Fishery Sciences)
Rainbow trout (Oncorhynchus mykiss) is a hypoxia-sensitive fish, and its growth, behavior, metabolism, and immunity are affected in hypoxic environments. To elucidate the effects of hypoxic stress on the heart of rainbow trout, biochemical indices and hypoxia-related gene expression were measured during moderate (4.5±0.1 mg/L) and severe hypoxia (3.0±0.1 mg/L) stress for 4 h, 8 h, 12 h, and 24 h; moderate hypoxia for 1 month (TMM); severe hypoxia for 1 month (TMM); and reoxygenation (8.5±0.1 mg/L) for 12 h and 24 h using enzyme activity assays and quantitative real time polymerase chain reaction (RT-qPCR). The results showed that the pyruvate kinase (PK), total cholesterol (TC), lactic acid (LD), and glutamine aminotransferase (GPT) reactivates increased at 8 h, decreased at 24 h, and were significantly higher than the control levels after reoxygenation (P < 0.05) under moderate hypoxic stress. Under severe hypoxic stress, the succinate dehydrogenase (SDH) activities gradually increased and peaked at 8 h (P < 0.05). No significant difference was observed between the control at 24 h and after reoxygenation (P > 0.05). The adenosine triphosphatase (ATPase), lipase (LPS), TC, glutamic transaminase (GOT), and GPT reactivates decreased at 12 h and recovered to normal levels after reoxygenation (P > 0.05). The PK, TC, lactate dehydrogenase (LDH), and GPT reactivates were significantly higher in the TMM and TMS groups than those in the control group (P < 0.05). The expressions of succinate dehydrogenase gene (sdh), factor inhibiting hypoxia-inducible factor-1 (fih1), and hypoxia-inducible factor-1α (hif-1α) were significantly increased at 8 h compared to those of the control (P < 0.05) and returned to normal reactivates after reoxygenation. Under severe hypoxic stress, lactate dehydrogenase gene (ldh), pyruvate kinase gene (pk), sdh, hif-1α, proline hydroxylase domain protein 2 (egln-1), and von Hippel-Lindau (vhl) expressions were significantly increased at 24 h (P < 0.05) compared to those under moderate hypoxic stress. Compared with those of the control group, ldh, pk, sdh, hif-1α, egln-1, and vhl expressions were significantly decreased in the TMM and TMS groups under moderate hypoxic stress with no significant differences (P > 0.05). pk, sdh, and vhl were significantly increased under severe hypoxic stress (P < 0.05). This study indicated that varying levels of dissolved oxygen led to changes in biochemical indices and in the expression of hypoxic-related genes in the heart of rainbow trout. Hypoxic stress affected the cardiac metabolism of rainbow trout, which affected the normal metabolism level and caused damage. Under hypoxic stress, the rainbow trout were able to provide feedback regulation of hypoxic stress through the high expression pattern of hypoxic-related, which prevents the heart from being in a constant state of hypoxic stress, allowing the organism to quickly return to a stable state and perform its normal physiological function. This study provides basic data to further elucidate the regulatory mechanism of cardiac metabolism in rainbow trout under hypoxic stress, it has guiding significance for the intensive and healthy breeding of this fish and the selection and breeding of new hypoxia-tolerant species in the future.